The Acoustical Analysis of Insertion Losses of Ceiling Materials - Enobong Patrick Obot; Rufus Chika Okoro; Daniel Effiong Oku; Christian Nlemchukwu Nwosu; Michael Ugwu Onuu (Proceedings of the Pakistan Academy of Sciences: A. Physical and Computational Sciences, 2023)
This study concentrates on measuring, analyzing and recommending the ceiling materials most suited for the reduction of distinct frequency noise levels with focus on rain noise. A frequency analyzer has been used to measure and obtained accurate sound level (LP) data of the rain noise outside, and inside five buildings with diverse acoustical ceiling materials in South Eastern Nigeria. It was done with and without the ceiling partition (or noise barrier) for the audio and narrow frequency band without contribution from other outdoor-related noise sources. Insertion losses of the ceiling materials were calculated using the data obtained from the measured LP. Result obtained from the analysis indicated that the ceiling material found to effectively reduce the noise levels from external noise source. The type for speech reception threshold frequencies of more than 125 Hz and higher audiometric range was moabi wood with peak LP of 21.20 dB at 500 Hz. While for lower frequencies where the ears are least responsive was plaster of Paris (POP) with peak LP of 12.61 dB at 62.5 Hz. This makes “moabi wood” most suitable in lecture rooms, conference halls and large auditoriums as ceiling material, in consideration of its capability to provide notable attenuation of rain noise within the building. This is in accordance with several other studies done on this subject. In general, at much low frequencies and frequencies greater than 2k Hz significant reduction in the rain noise level was observed.